Spanish Criminal Law in Sexual Crimes Committed in the Metaverse: Applicability and solutions to a present and future problem - Vasco Gómez, Antonio (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The Metaverse is considered the next evolution of the Internet for providing users with an immersive experience in a virtual world not seen before on the Internet. This new virtual experience will allow users to be part of a new reality that only exists through the screen of a device. Some examples of activities that emerged in the early days of the Internet and virtual reality could be considered sexual crimes against women. In order to protect potential victims and to promote the use of this new virtual experience among women, these criminal actions should be prosecuted under the Spanish Law.